LATIHAN EXERCISE WITH GROUPS OF 3 DAN EXERCISE WITH GROUPS OF 4 DAPAT MENIGKATKAN KEMAMPUAN PASSING SEPAK BOLA - Wardani, Intan Kusuma (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Football is a game that is played by kicking the ball by the player, by kicking it into the goal and aiming to get the ball into the opponent's goal. Passing is one of the basic techniques that must be mastered by soccer players. The results of observations in the field are still many players who have not passed well. The formulation of the problem in this study is whether there is an effect of exercise exercises with groups of 3 and exercises with groups of 4, and which exercises have more influence on football passing ability at the Pasirmas Football School in Nganjuk district in 2022. The purpose of this study was to determine the effect of exercises with groups of 3 and exercise with groups of 4 on football passing skills at the Pasirmas Football School in Nganjuk district in 2022. This study used an action test with a research design, namely a two group pretest-posttest design. The population in this study amounted to 80 students and a sample of 30 students. Implementation of the assessment is done by passing low to the target. Passing is said to be right if it enters the predetermined target through the specified legal line. This test is intended to measure the accuracy of passing down using the inside of the foot. The research data were analyzed using SPSS version 26. Group 3 t-test results obtained significant values (2-tailed) < 0.05: 0.000 < 0.05 and group 4 significant values (2-tailed) < 0.05 : 0.000 < 0.05. So this result shows that there is a significant difference. Based on the difference in the average post-test data for groups 3 and 4, it was obtained a significant value (2-tailed) < 0.05 : 0.000 < 0.05 with the percentage increase in group 4 being 0.70% and group 3 by 1.33%. Based on the results of the analysis, it can be concluded that exercise exercises with groups of 4 are more influential than exercises with groups of 3 on passing skills at the Pasirmas football school in Nganjuk Regency.